ANALISIS KEPUTUSAN KONSUMEN TERHADAP PENGGUNAAN JASA SEND MEULABOH - Mellyan, Mellyan; Agustina, Nadya (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2020)
Send Meulaboh the first online motorcycle taxi to operate in Meulaboh. This study aims to determine the analysis of consumer decisions on the use of Send Meulaboh services on students of the Teungku State Islamic University Dirundeng Meulaboh. The type of data used in this study is qualitative data using the Field Research and Library Research methods which are sourced from primary and secondary data. Data collection techniques used were interviewing, observing and searching books, journals, online media and related articles. Researchers conducted interviews by giving several questions to students who use the Meulaboh send service. The results showed the vendor control system (efficiency, price and quality) and marketing stimulation (product, price and promotion) seemed very closely related to the reasons for using Send Meulaboh services.